2000
DOI: 10.1103/physrevb.61.7996
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties of strongly correlated metals: A dynamical mean-field approach

Abstract: The temperature dependence of the transport properties of the metallic phase of a frustrated Hubbard model on the hypercubic lattice at half-filling is calculated. Dynamical mean-field theory, which maps the Hubbard model onto a single impurity Anderson model that is solved self-consistently, and becomes exact in the limit of large dimensionality, is used. As the temperature increases there is a smooth crossover from coherent Fermi liquid excitations at low temperatures to incoherent excitations at high temper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
254
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 222 publications
(277 citation statements)
references
References 83 publications
(123 reference statements)
22
254
1
Order By: Relevance
“…2,46,47 Recently two approaches were brought forward both based on a quarter-filled extended Hubbard model that includes the interaction V between molecules on the same but also different dimers. In general, within Hubbard-type models there is no contribution from spins to optics; however, besides single electron conductivity, singlets might form which move around leading to an additional contribution to the optical conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…2,46,47 Recently two approaches were brought forward both based on a quarter-filled extended Hubbard model that includes the interaction V between molecules on the same but also different dimers. In general, within Hubbard-type models there is no contribution from spins to optics; however, besides single electron conductivity, singlets might form which move around leading to an additional contribution to the optical conductivity.…”
Section: Discussionmentioning
confidence: 99%
“…8,[15][16][17]47 This suggests that these systems undergo a crossover from a bad metal regime for T Ͼ T 0 to a renormalized Fermi liquid below T 0 . However, we will show below ͑also see Fig.…”
Section: ͑13͔͒mentioning
confidence: 99%
“…Many features of the metallic phase agree well with the predictions of dynamical meanfield theory ͑DMFT͒ 14 which describes the crossover from a "bad metal" at high temperatures to a Fermi liquid as the temperature is lowered. [15][16][17] This crossover from incoherent to coherent intralayer 18 transport has been observed in a number of experiments such as resistivity, 17 thermopower, 15,19 and ultrasonic attenuation. 20,21 The existence of coherent quasiparticles is also apparent from the observed magnetic quantum oscillations at low temperatures in -͑ET͒ 2 X.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in many strongly correlated systems, such as the organic superconductors, 59 the charge transport is incoherent at high temperatures-this leads to a resistivity with a broad maximum slightly above the temperature where quasiparticle coherence is lost. 60 Above, we have shown that the slave boson theory of Hamiltonian ͑2͒ produces two bands. We will assume that some features of these bands survive even in the exact solution even if the simple single particle states of the slave boson theory do not.…”
Section: E a Picture Of Na 05 Coomentioning
confidence: 99%